Analisis Puisi “Aku Membawa Angin” Karya Heri Isnaini Dengan Menggunakan Pendekatan Semiotik - Dedi Soepandi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
Semiotically, poetry is a systematic and meaningful structure of signs determined by convention. Understanding poetry is nothing other than understanding the meaning of poetry. The meaning of poetry is a work that arises from language which is arranged based on literary structure according to its conventions. Therefore, to study poetry, it is necessary to conduct a semiotic analysis of the land, remembering that poetry is a structure of meaningful signs. The semiotic approach is considered capable of expressing the meaning contained in poetry, so this approach has received a lot of attention, namely with the research that has been produced. This article aims to discuss the hidden meaning of poetic texts through discussion and explanation from a semiotic perspective. This theory is used as a basis for explaining poetry in terms of the signs and interpretations thereof. The method used is descriptive qualitative with a focus on poetry as the object and research data. The results of this research show that the poem "Aku Brings the Wind" by Heri IsnaIni has a strong structure with signs that form meaning. The concept of determination is the dominant theme that builds the meaning of the poem as a whole. Thus, it is hoped that this research will open up research that utilizes semiotic theory in discussing poetry and other literary texts.